Thermal Balance Analysis of a Micro-Thermoelectric Gas Sensor Using Catalytic Combustion of Hydrogen - Daisuke Nagai; Takafumi Akamatsu; Toshio Itoh; Noriya Izu; Woosuck Shin (Sensors, 2014)
A thermoelectric gas sensor (TGS) with a combustion catalyst is a calorimetric sensor that changes the small heat of catalytic combustion into a signal voltage. We analyzed the thermal balance of a TGS to quantitatively estimate the sensor parameters. The voltage signal of a TGS was simulated, and the heat balance was calculated at two sections across the thermoelectric film of a TGS. The thermal resistances in the two sections were estimated from the thermal time constants of the experimental signal curves of the TGS. The catalytic combustion heat Qcatalyst required for 1 mV of ∆Vgas was calculated to be 46.1 μW. Using these parameters, we find from simulations for the device performance that the expected Qcatalyst for 200 and 1,000 ppm H2 was 3.69 μW and 11.7 μW, respectively.